Drug-Induced Lupus Erythematosus Associated with Proton Pump Inhibitor - Chinnusamy, Manokaran; Viswanathan, Ram Arvind; Janakiraman, Sathiyanarayanan; Elayidath, Roshna (Journal of Health and Allied Sciences NU, 2020)
Drug-induced lupus erythematosus is an autoimmune phenomenon where the drug exposure leads to the development of systemic lupus erythematous like clinical features. Drug-induced lupus erythematosus can be divided into systemic lupus erythematous, subacute cutaneous lupus erythematous, and chronic cutaneous lupus erythematous. Here, we report a case of a 29-year-old female presented with systemic lupus erythematous due to chronic use of proton pump inhibitors, which is considered to be very rare.
Keywords: drug-induced lupus; pantoprazole; proton pump inhibitors